Application Of Fun Learning Method to Improve Learning Outcomes In Al-Qur’an And Hadits Subjects - Ati Azizah, Nur; Carlian, Yayan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
The main problem in this study is how to improve student learning outcomes in learning al-Qur;an and Hadith in class II MI Al-Hidayah. This can occur because the learning process rarely uses modern methods and always uses conventional methods that do not actively involve students in the learning process. The characteristics of students are different so that the method is not suitable and results in student learning outcomes not reaching the maximum limit. Based on the results of data analysis, it was concluded that students' learning outcomes before using the fun learning method were still low. This can be seen from the average score obtained which is 49.5 and the classical learning completeness is only 15%. The learning process using the fun learning method was well implemented. This can be seen from the average percentage value of student activity in cycle I obtained by 64.3% and increased in cycle II with an average percentage value of 85.27%. Likewise, teacher activity in cycle I obtained an average percentage value of 55.5% and increased in cycle II with an average percentage of teacher activity of 83.5%. The student learning outcomes after the application of the fun learning method in cycle I obtained an average score of 67.50 and increased in cycle II with an average score of 80.75. So it can be concluded that using the fun learning method can improve student learning outcomes.